Exendin-4 enhances GLP-1 signaling and reduces anxiety-like behaviors in male heroin withdrawal mice - Yang Xiang; Xiaowei Yan; Rongrong Li; Chunlu Li; Dan Yin; Cancan Luo; Yingqi Xiong; Yan Hong; Yixin Li; Baijuan Xia (PLoS ONE, 2026)
Anxiety and depression significantly contribute to heroin relapse, and addressing these issues could lower relapse rates. The basolateral amygdala (BLA) and nucleus tractus solitarius (NTS) are involved in regulating these emotions, but the molecular mechanisms during heroin withdrawal are not yet understood. Subcutaneous injection of heroin into C57BL/6J mice to simulate chronic dependence, withdrawal, and Exendin-4 treatment. Assess anxiety and depression-like behaviors using open field test (OFT), elevated plus maze (EPM), forced swimming test (FST), and tail suspension test (TST). Analyze neuronal and protein expression changes in the BLA brain area with Western blotting (WB) and immunofluorescence staining. Heroin dependence reduces glutamatergic neurons in BLA without affecting anxiety and depression-like behaviors, due to the inhibitory effect of heroin reward. During withdrawal, GLP-1 secretion by the NTS rises, increasing c-Fos and GLP-1 receptor expression in glutamatergic neurons of BLA, linked to heightened anxiety but not depression. A 7-day treatment with Exendin-4 (2 µg/kg) alleviates anxiety in withdrawal mice by downregulating GLP-1 signaling in the NTS-BLA circuit, indicating GLP-1’s role in regulating anxiety during heroin withdrawal. GLP-1 receptors within BLA may serve as molecular targets for modulating emotional states, thereby offering empirical support for strategies aimed at preventing heroin relapse.